Multi-objective bees algorithm for portfolio diversification - Farid, Fajri; Linda Rassiyanti; Rohmi Dyah Astuti; Ade Lailani (Universitas Islam Negeri Raden Intan Lampung, 2025)
Portfolio diversification is the practice of spreading investments across different types of stocks or sectors to reduce overall risk. The basic principle is that the poor performance of one stock asset can be offset by the satisfactory performance of another stock asset. This study uses the Bees Algorithm for portfolio optimization problems, aiming to discover the combination of stock proportions in a portfolio that maximizes stock returns and minimizes risk. Then, the Sharpe ratio value is calculated and compared with conventional methods. The expected return, risk, and Sharpe ratio values for the portfolio generated using the Bees algorithm are 0.178007%, 2.353956%, and 0.0663484322, respectively. According to the results, the Bees Algorithm had better results and performance than conventional methods. As a result, the Bees Algorithm outperforms conventional approaches.